Positive electrode, battery, and method for manufacturing a positive electrode

JP2026165249APending Publication Date: 2026-10-14DENKA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025057536
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0009】 本開示によれば、内部抵抗が小さく、且つ、放電レート特性に優れた二次電池を得ることができる正極を提供することができる。また、本開示は、上記正極を備える電池を提供することができる。また、本開示は、上記正極の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165249000001
    Figure 2026165249000001
Patent Text Reader

Abstract

To provide a positive electrode that enables the production of a secondary battery with low internal resistance and excellent discharge rate characteristics. [Solution] A positive electrode comprising a current collector and a positive electrode material supported by the current collector, wherein the positive electrode material contains carbon black, carbon nanotubes, an active material, and a binder, the carbon black content in the positive electrode material is 25-60% by mass based on the total content of carbon black and carbon nanotubes, and the porosity of the positive electrode material is 30-40%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to a positive electrode, a battery, and a method for manufacturing a positive electrode. [Background technology]

[0002] Due to the growing environmental and energy concerns, there is a surge in the development of technologies aimed at realizing a low-carbon society that reduces reliance on fossil fuels. Such technological developments are diverse and include the development of low-emission vehicles such as hybrid electric vehicles (HEVs) and electric vehicles (EVs), the development of renewable energy power generation and storage systems such as solar and wind power generation, and the development of next-generation power grids that efficiently supply electricity and reduce transmission losses.

[0003] One of the key devices required for these technologies is the battery, and such batteries need high energy density to miniaturize the system. They also need high output characteristics to enable stable power supply regardless of ambient temperature. Furthermore, they need good cycle characteristics to withstand long-term use. For these reasons, there is a rapid shift from conventional lead-acid batteries, nickel-cadmium batteries, and nickel-metal hydride batteries to lithium-ion secondary batteries, which have higher energy density, output characteristics, and cycle characteristics.

[0004] Incidentally, since EVs drive their vehicles by discharging the battery to power the motor, EV batteries require a capacity that allows for long-term discharge and high cycle characteristics. For example, Patent Document 1 describes a conductive material consisting of carbon black with an average particle size of 1 nm to 100 nm, a dibutyl phthalate oil absorption capacity of 50 ml / 100 g or more, and an iodine adsorption capacity of 2000 mg / g or less, and a material with an average fiber diameter of 0.01 μm to 10 μm, an average fiber length of 1 μm to 200 μm, and a true density of 1.8 g / cm³. 3As described above, it is disclosed that by using a mixture with graphitized carbon fibers whose X-ray diffraction parameter d(002) is 0.345 nm or less, the obtained non-aqueous electrolyte battery has high cycle characteristics, long life, and large-current rapid chargeability.

Prior Art Document

Patent Document

[0005]

Patent Document 1

Summary of the Invention

Problem to be Solved by the Invention

[0006] In contrast to EVs, HEVs use both a gasoline-driven engine and a battery-driven motor. Therefore, compared with batteries for EVs, performance for long-time discharge is not essential for batteries for HEVs. Accordingly, compared with batteries for EVs, batteries for HEVs are required to be lightweight and manufactured at low cost. In addition, in order to improve the acceleration performance and the like of HEVs, batteries for HEVs are required to have improved instantaneous output performance (for example, reduced internal resistance, discharge rate characteristics, etc.).

[0007] The present disclosure aims to provide a positive electrode that can obtain a secondary battery with low internal resistance and excellent discharge rate characteristics. The present disclosure also aims to provide a battery including the above positive electrode. The present disclosure further aims to provide a method for manufacturing the above positive electrode.

Means for Solving the Problem

[0008] The present disclosure relates to, for example, the following <1> to <7>. <1>A positive electrode comprising a current collector, and a positive electrode material supported by the current collector, wherein the positive electrode material contains carbon black, carbon nanotubes, an active material, and a binder, the content of the carbon black in the positive electrode material is 25 to 60 mass% based on the total content of the carbon black and the carbon nanotubes, and the porosity of the positive electrode material is 30 to 40%. <2>The carbon black has a BET specific surface area of 100 to 400 m 2 / g, a crystallite size (Lc) of 15 to 26 Å, and an average primary particle diameter of 17 to 30 nm, the positive electrode according to <1>. <3>The positive electrode according to <1> or <2>, wherein the carbon nanotubes have an average diameter of 5 to 15 nm. <4>The basis weight of the positive electrode material is 7.5 to 12.5 mg / cm 2 , the positive electrode according to any one of <1> to <3>. <5>A battery comprising the positive electrode according to any one of <1> to <4>. <6>The battery according to <5>, which is for hybrid electric vehicles or consumer products. <7>A method for producing the positive electrode according to any one of <1> to <4>, the method comprising a first step of applying a coating liquid containing carbon black, carbon nanotubes, an active material, a binder and a liquid medium onto a current collector, and drying the applied coating liquid to form a coating film containing the carbon black, the carbon nanotubes, the active material and the binder on the current collector, and a second step of pressing the coating film to form the positive electrode material on the current collector, wherein the content of the carbon black in the coating liquid is 25 to 60 mass% based on the total content of the carbon black and the carbon nanotubes, and the second step is a step of pressing the coating film such that the porosity of the positive electrode material becomes 30 to 40%. Advantageous Effects of the Invention

[0009] This disclosure provides a positive electrode that can be used to obtain a secondary battery with low internal resistance and excellent discharge rate characteristics. Furthermore, this disclosure provides a battery equipped with the above positive electrode. Furthermore, this disclosure provides a method for manufacturing the above positive electrode. [Modes for carrying out the invention]

[0010] One embodiment of this disclosure will be described in detail below.

[0011] In this specification, when a tilde symbol (~) is used, for example, "x~y" (where x and y are numerical values), it means "more than or equal to x and less than or equal to y". Specifically, "25~60 mass%" means "more than 25 mass% and less than or equal to 60 mass%".

[0012] The positive electrode according to this embodiment includes a current collector (positive electrode current collector) and a positive electrode material supported by the current collector, wherein the positive electrode material contains carbon black, carbon nanotubes, an active material (positive electrode active material), and a binder. The carbon black content in the positive electrode material is 25 to 60% by mass, based on the total content of carbon black and carbon nanotubes. The porosity of the positive electrode material is 30 to 40%.

[0013] The basic role of conductive materials is to impart conductivity to the positive electrode active material, which otherwise has poor conductivity. In addition, in secondary batteries (for example, lithium-ion secondary batteries), the positive electrode active material expands and contracts due to repeated charging and discharging, causing the contact points between the positive electrode active materials to gradually be lost. Conductive materials also play a role in connecting the positive electrode active materials that have lost their contact points, thereby preventing the loss of conductivity.

[0014] The inclusion of carbon black in the cathode material facilitates the formation of conductive pathways between active materials and makes it easier to retain non-aqueous electrolyte near the active materials. Furthermore, the inclusion of carbon nanotubes in the cathode material facilitates the formation of conductive pathways on the surface of the active materials, thus forming an electrode structure and making it easier to obtain an electrode with good conductive pathways and ionic conductivity.

[0015] According to the positive electrode of this embodiment, a secondary battery suitable for use in HEVs can be obtained, which has low internal resistance and excellent discharge rate characteristics.

[0016] In this embodiment, since the cathode material has a porosity of 30-40%, the cathode material is lightweight, and manufacturing costs are reduced. Furthermore, in this embodiment, by controlling the blending ratio of carbon black and carbon nanotubes, it is possible to achieve both low internal resistance and excellent discharge rate characteristics while maintaining the aforementioned porosity.

[0017] The carbon black may be any carbon black commonly used as a conductive material for batteries, such as acetylene black, furnace black, or channel black. From the viewpoint of having excellent purity and easily obtaining excellent battery characteristics, acetylene black is preferred.

[0018] The BET specific surface area of ​​carbon black is, for example, 100-400 m². 2 It may be / g. The BET specific surface area of ​​the carbon blank is 100m². 2 Having a BET specific surface area of ​​400 m² or more increases the number of electrical contacts with the active material and conductive material, resulting in a better conductivity-enhancing effect and making it easier to obtain superior battery characteristics. 2 / g or less, the interaction between the solvent and the conductive material and between the conductive materials is reduced, which facilitates uniform dispersion in the active material, making it easy to form a conductive path, and thus excellent battery characteristics can be more easily obtained. The BET specific surface area of carbon black can be measured by the static volumetric method in accordance with JIS Z8830 using nitrogen as the adsorbate.

[0019] The BET specific surface area of carbon black is, from the viewpoint of further reducing the internal resistance of the battery and from the viewpoint of more excellent discharge rate characteristics of the battery, 130 m 2 / g or more, 150 m 2 / g or more, 170 m 2 / g or more, 200 m 2 / g or more, 240 m 2 / g or more, or 280 m 2 / g or more. The BET specific surface area of carbon black is, from the viewpoint of further reducing the internal resistance of the battery and from the viewpoint of more excellent discharge rate characteristics of the battery, 370 m 2 / g or less.

[0020] The crystallite size (Lc) of carbon black may be, for example, 15 to 26 Å. When the crystallite size (Lc) is 15 Å or more, π electrons easily move through the crystal layers, which facilitates the formation of a conductive path that carries electrons flowing from the current collector to the active material, making excellent battery characteristics easier to obtain. In addition, when the crystallite size (Lc) is 15 Å or more, oxidative decomposition is less likely to occur even when used under high voltage. When the crystallite size (Lc) is 26 Å or less, the particle shape of carbon black tends to be more rounded, which reduces the interaction between particles and facilitates uniform dispersion in the active material. Since a conductive path is easily formed, excellent battery characteristics can be more easily obtained. The crystallite size (Lc) of carbon black can be measured in accordance with JIS R7651. The crystallite size (Lc) of carbon black means the crystallite size in the c-axis direction of the carbon black crystal layer.

[0021] The crystallite size (Lc) of carbon black may be 24 Å or less, 22 Å or less, or 20 Å or less, from the viewpoint of reducing the internal resistance of the battery and improving the discharge rate characteristics of the battery. The crystallite size (Lc) of carbon black may be 16 Å or more, 18 Å or more, or 20 Å or more.

[0022] The average primary particle diameter of carbon black may be, for example, 17 to 30 nm. An average primary particle diameter of 17 nm or greater reduces the interaction between the solvent and the conductive material, and between conductive materials, making it easier to uniformly disperse in the active material. This facilitates the formation of conductive pathways, thus making it easier to obtain superior battery characteristics. An average primary particle diameter of 30 nm or less increases the number of electrical contact points with the active material and conductive material, resulting in a better conductivity-imparting effect, thus making it easier to obtain superior battery characteristics. The average primary particle diameter of carbon black refers to the average value of the equivalent circle diameter measured from images of carbon black observed with a transmission electron microscope (TEM). Specifically, it is obtained by using a JEM-2000FX transmission electron microscope (manufactured by JEOL Ltd.), taking 10 images of carbon black at 100,000x magnification, and measuring the equivalent circle diameter of 200 randomly selected primary particles of carbon black from the resulting images using image analysis, then taking the arithmetic mean.

[0023] The average primary particle size of the carbon black may be 26 nm or less, 24 nm or less, 22 nm or less, or 20 nm or less, from the viewpoint of reducing the internal resistance of the battery and improving the discharge rate characteristics of the battery. The average primary particle size of the carbon black may also be 18 nm or more.

[0024] When the peak area of ​​the peak with mass number m / z 57 detected by thermal desorption gas analysis of carbon black is denoted as S1, and the peak area of ​​the peak with mass number m / z 128 is denoted as S2, the ratio of peak area S2 to peak area S1 (S2 / S1) may be, for example, 0.2 to 1.9. The ratio (S2 / S1) indicates the proportion of organic components adsorbed on the surface of the carbon black. When the ratio (S2 / S1) is 1.9 or less, the amount of organic components adsorbed on the surface of the carbon black is sufficiently small, and the decrease in conductivity caused by the organic components trapping π electrons is significantly suppressed. Furthermore, when the ratio (S2 / S1) is 0.2 or more, the organic components adsorbed on the surface of the carbon black act as a dispersant, improving dispersibility in the solvent and further reducing slurry viscosity. The peak areas S1 of the peak with mass number m / z 57 and S2 of the peak with mass number m / z 128 can be measured by generated gas mass spectrometry (EGA-MS). For example, by setting carbon black in a gas chromatograph-mass spectrometer equipped with a pyrolysis device, holding it at 50°C for 5 minutes in a He flow at atmospheric pressure, then increasing the temperature to 800°C at 80°C / min, and performing mass analysis of the components desorbed by the temperature increase, the peak area S1 of the peak with mass number m / z 57 and the peak area S2 of the peak with mass number m / z 128 can be measured.

[0025] The ratio (S2 / S1) may be 1.5 or less, 1.0 or less, 0.8 or less, 0.6 or less, 0.5 or less, 0.4 or less, or 0.3 or less, from the viewpoint of reducing the internal resistance of the battery and improving the discharge rate characteristics of the battery. The ratio (S2 / S1) may be 0.25 or more, or 0.3 or more.

[0026] The volume resistivity of carbon black may be, for example, 0.30 Ω·cm or less, or 0.25 Ω·cm or less, from the viewpoint of superior conductivity. The volume resistivity of carbon black is measured, for example, under compression under a load of 7.5 MPa.

[0027] The ash content and moisture content of carbon black are not particularly limited. The ash content of carbon black may be, for example, 0.04% by mass or less, based on the total mass of carbon black. The moisture content of carbon black may be, for example, 0.10% by mass or less, based on the total mass of carbon black.

[0028] Carbon black can be produced, for example, by a manufacturing method that includes a synthesis step of processing a raw material gas containing hydrocarbons in a cylindrical decomposition furnace to obtain carbon black, and a high-purity step of removing magnetic foreign matter from the carbon black obtained in the synthesis step using a magnet.

[0029] In the synthesis process, the raw material gas is treated in a cylindrical cracking furnace. The cylindrical cracking furnace may, for example, include a pyrolysis section for carrying out the thermal decomposition reaction of hydrocarbons and a maturation section for modifying the pyrolysis reaction products. The cylindrical cracking furnace may further include a supply port for supplying the raw material gas to the pyrolysis section and a recovery port for recovering the carbon black produced from the maturation section.

[0030] In the pyrolysis section, it is preferable that the supplied raw material gas remains at a temperature of 1900°C or higher for 30 to 150 seconds. A residence time of 30 seconds or more ensures that the pyrolysis reaction is completed and that carbon aerosols are formed through the development of a chain structure. Furthermore, a residence time of 150 seconds or less suppresses the aggregation of carbon aerosols, making it easier to remove magnetic foreign matter in the high-purity process and thus easier to obtain high-purity carbon black.

[0031] In the maturation section, it is preferable that the pyrolysis reaction products supplied from the pyrolysis section remain at a temperature of 1700°C or higher for 20 to 90 seconds. A residence time of 20 seconds or more for the pyrolysis reaction products facilitates the modification of carbon aerosols and the development of aggregates, making it easier to obtain higher quality carbon black. Conversely, a residence time of 90 seconds or less for the pyrolysis reaction products suppresses the aggregation of carbon aerosols, making it easier to remove magnetic foreign matter in the high-purity process and thus easier to obtain high-purity carbon black.

[0032] The residence times in the pyrolysis section and the maturation section can be appropriately adjusted by controlling the linear velocity of the flowing gas. It is preferable that the residence time in the maturation section be shorter than that in the pyrolysis section. That is, it is preferable that the linear velocity of the gas in the maturation section be faster than that in the pyrolysis section.

[0033] In this embodiment, the raw material gas preferably contains acetylene as a carbon source. The carbon source (e.g., acetylene) content in the raw material gas is, for example, 10% by volume or more, preferably 20% by volume or more, more preferably 30% by volume or more, and may be 100% by volume. The content of each component in the raw material gas is expressed as a volume ratio based on the volume at 100°C and 1 atmosphere.

[0034] The raw material gas may further contain other hydrocarbons besides the carbon source (e.g., acetylene). Examples of other hydrocarbons include methane, ethane, propane, ethylene, propylene, butadiene, benzene, toluene, xylene, gasoline, kerosene, light oil, and heavy oil. By adding these other hydrocarbons, the reaction temperature can be changed to increase or decrease the specific surface area of ​​the carbon black. The other hydrocarbons are preferably selected from the group consisting of aromatic hydrocarbons such as benzene and toluene, and unsaturated hydrocarbons such as ethylene and propylene.

[0035] When the raw material gas contains acetylene and other hydrocarbons, the content of the other hydrocarbons is, for example, 0.1 to 99 parts by volume, preferably 0.2 to 50 parts by volume, and more preferably 0.3 to 30 parts by volume, per 100 parts by volume of acetylene.

[0036] The raw material gas may further contain water vapor, oxygen, hydrogen, carbon dioxide, etc. It is preferable to use high-purity gases with a purity of 99.9% or higher. Using such high-purity gases tends to facilitate the production of carbon black with fewer magnetic impurities and stable BET specific surface area and oil absorption.

[0037] The water vapor content may be, for example, 0 to 80 parts by volume, preferably 0.1 to 70 parts by volume, more preferably 1 to 60 parts by volume, and even more preferably 3 to 55 parts by volume, relative to 100 parts by volume of the carbon source (e.g., acetylene) in the raw material gas. When the water vapor content is within the above range, the BET specific surface area of ​​the carbon black tends to increase.

[0038] In the synthesis process, it is preferable to supply oxygen gas to the pyrolysis section along with the raw material gas, and it is even more preferable to supply oxygen gas to the pyrolysis section by injecting oxygen gas from around the supply port to which the raw material gas is supplied.

[0039] A cylindrical cracking furnace preferably has an oxygen gas injection port near the raw material gas supply port, and more preferably has a plurality of injection ports arranged at equal intervals surrounding the supply port. The number of injection ports is preferably 3 or more, more preferably 3 to 8.

[0040] Furthermore, the cylindrical decomposition furnace may be equipped with a nozzle having a multi-tube structure (e.g., a double-tube structure, a triple-tube structure, etc.) that has a raw material gas supply port and an injection port for injecting oxygen gas from around it. In the case of a double-tube structure, for example, the raw material gas may be injected from the gap on the inner cylinder side and the oxygen gas from the gap on the outer cylinder side. In the case of a triple-tube structure consisting of an inner tube, a middle tube, and an outer tube, for example, the oxygen gas may be injected from the gap formed by the outer wall of the middle tube and the inner wall of the outer tube, and the raw material gas may be injected from the remaining gap.

[0041] The amount of oxygen gas injected is not particularly limited, provided that the carbon black production yield is not considered. Carbon black can be produced even if more oxygen gas is injected than necessary. The amount of oxygen gas injected may be, for example, 0 to 300, 0 to 250, 0 to 220, or 0 to 200 parts per 100 parts per volume of carbon source (e.g., acetylene) in the raw material gas, preferably 0.1 to 190 parts, more preferably 0.5 to 180 parts, and even more preferably 1 to 160 parts. When the amount of oxygen gas injected increases, the BET specific surface area of ​​the carbon black and the above ratio (S1 / S2) tend to increase, and when the amount of oxygen gas injected decreases, the primary particle size of the carbon black tends to increase.

[0042] In the synthesis process, the primary particle size, BET specific surface area, and crystallite size (Lc) of the resulting carbon black can be adjusted, for example, by adjusting the addition rate of hydrocarbons other than acetylene, the amount of oxygen gas injected, etc.

[0043] The high-purity process is a process of removing magnetic foreign matter from the carbon black obtained in the synthesis process using a magnet. The high-purity process may be a process of removing magnetic foreign matter from the carbon black obtained in the synthesis process by bringing it into contact with a magnet or by placing it near a magnet (for example, by passing it near a magnet).

[0044] The maximum surface magnetic flux density of the magnet is not particularly limited, but may be, for example, 700 mT or more, preferably 1000 mT or more, and more preferably 1200 mT or more. This allows fine magnetic foreign matter attached to the carbon black to be more strongly attracted, making it easier to obtain carbon black with a lower nickel content. The upper limit of the maximum surface magnetic flux density of the magnet is not particularly limited, and may be, for example, 1400 mT or less.

[0045] The high-purity process may involve removing magnetic foreign matter from the carbon black so that the nickel content in the carbon black is 50 ppb or less (preferably 40 ppb or less, more preferably 30 ppb or less, and even more preferably 20 ppb or less). The nickel content in the carbon black may be, for example, 1 ppb or more, and from the viewpoint of cost and productivity, it may be 10 ppb or more, or even 15 ppb or more.

[0046] The carbon nanotubes may be the same carbon nanotubes commonly used as conductive materials for batteries.

[0047] The average diameter of carbon nanotubes may be, for example, 5 to 15 nm. If the average diameter of carbon black is 5 nm or greater, the interaction between the solvent and the conductive material, and between conductive materials, is reduced, making it easier to uniformly disperse in the active material. This facilitates the formation of conductive pathways, thus making it easier to obtain superior battery characteristics. If the average diameter of carbon black is 15 nm or less, the number of electrical contact points with the active material and conductive material increases, resulting in a better conductivity-imparting effect and making it easier to obtain superior battery characteristics.

[0048] The average diameter of carbon nanotubes may be 14 nm or less, 13 nm or less, or 12 nm or less, from the viewpoint of reducing the internal resistance of the battery and improving the discharge rate characteristics of the battery. The average diameter of carbon nanotubes may also be 6 nm or more. The average diameter of carbon nanotubes refers to the average value of the diameter measured based on images obtained when carbon nanotubes are observed with a transmission electron microscope (TEM). Specifically, it is obtained by using a transmission electron microscope JEM-2000FX (manufactured by JEOL Ltd.), taking 10 images of carbon nanotubes at a magnification of 200,000 times, measuring the diameter of 100 carbon nanotubes randomly selected from the obtained images by image analysis, and taking the arithmetic mean.

[0049] The BET specific surface area of ​​carbon nanotubes is, for example, 170-320 m². 2It may be / g. The BET specific surface area of ​​carbon nanotubes is 170m². 2 Having a BET specific surface area of ​​320 m² or more increases the number of electrical contact points with the active material and conductive material, resulting in a better conductivity-imparting effect and making it easier to obtain superior battery characteristics. 2 When the concentration is less than / g, the interaction between the solvent and the conductive material, and between conductive materials, is reduced, making it easier for the active material to disperse uniformly. This facilitates the formation of conductive pathways, thus making it easier to obtain superior battery characteristics. The BET specific surface area of ​​carbon nanotubes can be measured using the static capacity method in accordance with JIS Z8830, with nitrogen used as the adsorbate.

[0050] The BET specific surface area of ​​carbon nanotubes is 180m², from the perspective of reducing the internal resistance of the battery and improving the discharge rate characteristics of the battery. 2 / g or more, 190m 2 / g or more, 200m 2 / g or more, or 220m 2 It may be 300 m² or more. The BET specific surface area of ​​carbon nanotubes is 300 m² from the viewpoint of reducing the internal resistance of the battery and improving the discharge rate characteristics of the battery. 2 It may be less than / g.

[0051] The ratio of the average diameter of a carbon nanotube to its BET specific surface area (average diameter / BET specific surface area) is, for example, 0.01 to 0.068 nm / (m²). 2 The average diameter / BET specific surface area is the value obtained by dividing the average diameter of the carbon nanotube by the BET specific surface area of ​​the carbon nanotube. The average diameter / BET specific surface area is 0.01 nm / (m 2 Having a specific surface area of ​​0.068 nm / (m²) or more reduces entanglement between carbon nanotubes, making them easier to uniformly disperse in the active material. This facilitates the formation of conductive pathways, thus making it easier to obtain superior battery characteristics. 2By keeping the value below ( / g), the number of carbon nanotubes per unit weight increases, allowing electricity to flow more efficiently throughout the active material, thus making it easier to obtain superior battery characteristics.

[0052] The average diameter / BET specific surface area ratio is set to 0.06 nm / (m²) from the perspective of reducing the internal resistance of the battery and improving its discharge rate characteristics. 2 / g) or less, 0.055nm / (m 2 / g) or less, or 0.05nm / (m 2 The average diameter / BET specific surface area is set to 0.02 nm / (m²) from the viewpoint of reducing the internal resistance of the battery and improving the discharge rate characteristics of the battery. 2 It may be more than / g.

[0053] Carbon nanotubes can be produced, for example, by conventionally known carbon nanotube manufacturing methods. For instance, a powdered catalyst consisting of iron supported on magnesia (magnesium oxide) can be placed across the entire horizontal cross-section of a vertical reactor, methane can be flowed vertically through the reactor, and the methane and catalyst can be brought into contact at 500-1200°C. The resulting product (unoxidized carbon nanotubes) can then be oxidized.

[0054] The oxidation treatment of the above product may be, for example, a calcination treatment. The temperature of the calcination treatment is not particularly limited as long as carbon nanotubes containing the cathode material can be obtained, and may be, for example, 300 to 1000°C. The temperature of the calcination treatment is affected by the atmospheric gas, so it is preferable to perform the calcination treatment at a relatively low temperature when the oxygen concentration is high, and at a relatively high temperature when the oxygen concentration is low. Specifically, as a calcination treatment of the product, one method is to calcine under air within a range of ±50°C from the combustion peak temperature of the carbon nanotubes before oxidation treatment, but if the oxygen concentration is higher than that of air, calcination should be performed in a temperature range lower than the calcination peak temperature, and if the oxygen concentration is lower than that of air, a temperature range higher than the calcination peak temperature should be selected. In particular, when calcining the carbon nanotubes before oxidation treatment under air, it is preferable to do so within a range of ±15°C from the combustion peak temperature of the carbon nanotubes before oxidation treatment.

[0055] The oxidation treatment of the above product may be carried out with hydrogen peroxide, mixed acid, nitric acid, etc. For example, a method of treating the above product with hydrogen peroxide involves mixing the above product in 34.5% hydrogen peroxide solution to a concentration of 0.01 to 10% by mass, and reacting it at a temperature of 0 to 100°C for 0.5 to 48 hours. Alternatively, a method of treating the above product with mixed acid involves mixing the above product in a mixed solution of concentrated sulfuric acid and concentrated nitric acid (concentrated sulfuric acid:concentrated nitric acid = 3:1) to a concentration of 0.01 to 10% by mass, and reacting it at a temperature of 0 to 100°C for 0.5 to 48 hours. The mixing ratio of the mixed acid (concentrated sulfuric acid:concentrated nitric acid) can be adjusted within the range of 1:10 to 10:1 depending on the amount of single-walled carbon nanotubes in the above product. One method for treating the above product with nitric acid is to mix the above product with nitric acid at a concentration of 40-80% by mass so that it is present in a concentration of 0.01-10% by mass, and to react it at a temperature of 60-150°C for 0.5-48 hours.

[0056] By performing an oxidation treatment on the above product, impurities such as amorphous carbon and single-walled carbon nanotubes with low heat resistance can be selectively removed, improving the purity of several graphene layers, especially 2 to 5 layers of carbon nanotubes. At the same time, the oxidation treatment of the product adds functional groups to the surface of the carbon nanotubes, improving their affinity with the dispersion medium and additives, and thus improving their dispersibility. Among the above oxidation treatments, treatment using nitric acid is preferred.

[0057] The above oxidation treatment may be performed immediately after obtaining the carbon nanotubes before oxidation, or after another purification treatment. For example, when using iron / magnesia as a catalyst, the oxidation treatment may be performed after purification with an acid such as hydrochloric acid to remove the catalyst, or the oxidation treatment may be performed after purification to remove the catalyst.

[0058] The positive electrode material may further contain other conductive materials besides carbon black and carbon nanotubes, but it is preferable that the main conductive materials in the positive electrode material are carbon black and carbon nanotubes. The total proportion of carbon black and carbon nanotubes in the conductive materials in the positive electrode material may be, for example, 80% by mass or more, 90% by mass or more, 95% by mass or more, 97% by mass or more, or 99% by mass or more, or 100% by mass.

[0059] The total content of carbon black and carbon nanotubes in the cathode material may be, for example, 0.05% by mass or more, 0.1% by mass or more, 0.2% by mass or more, 0.3% by mass or more, or 0.4% by mass or more, based on the total mass of the cathode material. Furthermore, the total content of carbon black and carbon nanotubes in the cathode material may be, for example, 5% by mass or less, 4% by mass or less, 3% by mass or less, 2% by mass or less, or 1% by mass or less, based on the total mass of the cathode material.

[0060] The carbon black content in the positive electrode material is 25% by mass or more, based on the total content of carbon black and carbon nanotubes, and may be 27% by mass or more, or 29% by mass or more, from the viewpoint of further reducing the internal resistance of the battery and improving the discharge rate characteristics of the battery. Furthermore, the carbon black content in the positive electrode is 60% by mass or less, based on the total content of carbon black and carbon nanotubes, and may be 58% by mass or less, 56% by mass or less, 54% by mass or less, or 52% by mass or less, from the viewpoint of further reducing the internal resistance of the battery and improving the discharge rate characteristics of the battery, and may be 50% by mass or less, 45% by mass or less, or 40% by mass or less.

[0061] The positive electrode material contains an active material (positive electrode active material). The active material is not particularly limited and can be appropriately selected from known active materials.

[0062] The active material is a substance capable of reversibly intercalating and deintercalating cations, for example, with a volume resistivity of 1 × 10⁻⁶. 4 This may be a lithium-containing composite oxide or lithium-containing polyanionic compound containing manganese of Ω·cm or more. Examples of manganese-containing lithium-containing composite oxides include LiMnO2, LiMnO3, LiMn2O3, Li 1+x Mn 2-x Lithium manganese oxide such as O4 (where x = 0 to 0.33); LiMn x Ni y Co z O2 (however, x+y+z=1, 0≦y<1, 0≦z<1, 0≦x<1), Li 1+x Mn 2-x-y M y O4 (where x = 0 to 0.33, y = 0 to 1.0, 2-xy > 0), LiMn 2-x M xExamples of composite oxides containing one or more transition metal elements include O2 (where x = 0.01 to 0.1) and Li2Mn3MO8. Examples of lithium-containing polyanionic compounds include LiFePO4, LiMnPO4, and Li2MPO4F (where M is at least one metal selected from Co, Ni, Fe, Cr, and Zn). In each compositional formula, M is at least one selected from the group consisting of Fe, Co, Ni, Al, Cu, Mg, Cr, Zn, and Ta.

[0063] Average particle size of the active material (D 50 The average particle size (D) of the active material in the positive electrode material may be, for example, 20 μm or less, or 15 μm or less, from the viewpoint of obtaining a battery with sufficiently good bonding between the conductive material and the binder and excellent cycle characteristics. 50 ) can be measured by laser light scattering.

[0064] From the viewpoint of increasing the energy density of the battery, the content of the active material in the positive electrode material may be, for example, 85% by mass or more, 87.5% by mass or more, 90% by mass or more, 92.5% by mass or more, or 95% by mass or more, based on the total mass of the positive electrode material. From the viewpoint of increasing the output power of the battery, the content of the active material in the positive electrode material may be, for example, 99.85% by mass or less, 99.7% by mass or less, 99.4% by mass or less, 99.1% by mass or less, or 98.8% by mass or less, based on the total mass of the positive electrode material.

[0065] The positive electrode material contains a binder. Examples of binders in the positive electrode material include polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene copolymer, and (meth)acrylic acid ester copolymer. The polymer structure of the binder may be, for example, a random copolymer, an alternating copolymer, a graft copolymer, or a block copolymer. From the viewpoint of excellent dielectric strength, the binder may be polyvinylidene fluoride.

[0066] The binder content in the positive electrode material may be, for example, 0.1% by mass or more, 0.2% by mass or more, 0.4% by mass or more, 0.6% by mass or more, or 0.8% by mass or more, based on the total mass of the positive electrode material, from the viewpoint of improving the bonding properties of the positive electrode plate and making it easier to obtain a battery with superior cycle characteristics. The binder content in the positive electrode material may be, for example, 10% by mass or less, 8% by mass or less, 6% by mass or less, 4% by mass or less, or 2% by mass or less, based on the total mass of the positive electrode material, from the viewpoint of further reducing the resistance of the positive electrode plate and further improving the discharge rate characteristics of the battery.

[0067] The positive electrode material may further contain other additives besides the active material, conductive material, and binder. These other additives may, for example, be polyvinylpyrrolidone, polyvinylimidazole, polyethylene glycol, polyvinyl alcohol, polyvinyl butyral, carboxymethylcellulose, acetylcellulose, carboxylic acid-modified (meth)acrylic acid ester copolymer, etc., from the viewpoint of improving dispersibility.

[0068] The content of other additives in the positive electrode material may be, for example, 5% by mass or less, 3% by mass or less, 1% by mass or less, 0.5% by mass or less, 0.1% by mass or less, or 0.05% by mass or less, based on the total mass of the positive electrode material, or it may be 0% by mass.

[0069] The porosity of the positive electrode material is 30-40%. A porosity of 30% or higher ensures ion diffusion pathways and reduces the internal resistance of the battery. As a result, it becomes possible to obtain a battery suitable for HEVs. A porosity of 40% or lower prevents excessive distance between active materials and ensures that conductive paths are not lost. The porosity of the positive electrode material may be 32% or higher, 33% or higher, or 34% or higher, and may also be 39% or lower, 38% or lower, or 37% or lower.

[0070] The basis weight of the positive electrode material is set to, for example, 2.5 mg / cm³, from the perspective of further improving battery capacity. 2 The above is acceptable, or 5 mg / cm³ 2 Above, or 7.5 mg / cm³ 2The above is also acceptable. The basis weight of the positive electrode material should be, for example, 20 mg / cm³, from the viewpoint of facilitating ion movement inside the battery. 2 The following may be used: 15 mg / cm³ 2 The following, or 12.5 mg / cm³ 2 The following is also acceptable.

[0071] The thickness of the positive electrode material may be, for example, 10 μm or more, 20 μm or more, or 30 μm or more, from the viewpoint of further improving battery capacity. The thickness of the positive electrode material may be, for example, 50 μm or less, 45 μm or less, or 40 μm or less, from the viewpoint of facilitating ion movement inside the battery.

[0072] Cathode materials can be manufactured by known methods. For example, they can be obtained by mixing carbon black, carbon nanotubes, active material, binder, and dispersion medium (and other additives) using a ball mill, sand mill, twin-screw kneader, orbital agitator, planetary mixer, disperser mixer, etc. Carbon black and carbon nanotubes may be added to the mixer separately or they may be mixed beforehand. When mixing carbon black, it may be in slurry form. A method for producing a carbon black slurry may include a step of mixing carbon black, dispersion medium (e.g., N-methyl-2-pyrrolidone), and dispersant (e.g., hydrogenated nitrile butadiene rubber).

[0073] The positive electrode according to this embodiment includes a current collector (positive electrode current collector). The positive electrode current collector may be a metal foil or a metal plate. Examples of metals included in the metal foil or metal plate include stainless steel, aluminum, nickel, iron, titanium, and the like.

[0074] The thickness of the positive electrode current collector may be, for example, 5 μm or more, or 10 μm or more. Alternatively, the thickness of the positive electrode current collector may be, for example, 30 μm or less, or 20 μm or less.

[0075] The thickness of the positive electrode may be, for example, 15 μm or more, 30 μm or more, or 40 μm or more, from the viewpoint of improving the discharge capacity of the battery. The thickness of the positive electrode may be, for example, 100 μm or less, 80 μm or less, or 60 μm or less, from the viewpoint of facilitating ion movement inside the battery.

[0076] The method for manufacturing a positive electrode according to this embodiment is a method for manufacturing the positive electrode described above, and may comprise a first step of applying a coating solution containing carbon black, carbon nanotubes, active material (positive electrode active material), a binder, and a liquid medium onto a current collector (positive electrode current collector), drying it to form a coating film containing carbon black, carbon nanotubes, active material, and a binder on the current collector, and a second step of pressing the coating film to form a positive electrode material on the current collector. The carbon black content in the coating solution is 25 to 60% by mass, based on the total content of carbon black and carbon nanotubes. The second step is a step of pressing the coating film so that the porosity of the positive electrode material is 30 to 40%.

[0077] The details of the carbon black, carbon nanotubes, active material, and binder in the method for manufacturing the positive electrode may be the same as those in the positive electrode material described above. Examples of liquid media include water, N-methyl-2-pyrrolidone, cyclohexane, methyl ethyl ketone, and methyl isobutyl ketone.

[0078] The content of each component in the coating solution may be adjusted as appropriate so that the content of each component in the positive electrode material falls within the range described above.

[0079] The total content of carbon black and carbon nanotubes in the coating solution may be, for example, 0.05% by mass or more, 0.1% by mass or more, 0.2% by mass or more, 0.3% by mass or more, or 0.4% by mass or more, based on the total mass of solids in the coating solution. The total content of carbon black and carbon nanotubes in the coating solution may be, for example, 5% by mass or less, 4% by mass or less, 3% by mass or less, 2% by mass or less, or 1% by mass or less, based on the total mass of solids in the coating solution.

[0080] The carbon black content in the coating solution is 25% by mass or more, based on the total content of carbon black and carbon nanotubes, and may be 27% by mass or more, or 29% by mass or more. Alternatively, the carbon black content in the coating solution is 60% by mass or less, based on the total content of carbon black and carbon nanotubes, and may be 58% by mass or less, 56% by mass or less, 54% by mass or less, or 52% by mass or less, and may be 50% by mass or less, 45% by mass or less, or 40% by mass or less.

[0081] The amount of active material in the coating solution may be, for example, 85% by mass or more, 87.5% by mass or more, 90% by mass or more, 92.5% by mass or more, or 95% by mass or more, based on the total mass of solids in the coating solution. The amount of active material in the coating solution may be, for example, 99.85% by mass or less, 99.7% by mass or less, 99.4% by mass or less, 99.1% by mass or less, or 98.8% by mass or less, based on the total mass of solids in the coating solution.

[0082] The binder content in the coating liquid may be, for example, 0.1% by mass or more, 0.2% by mass or more, 0.4% by mass or more, 0.6% by mass or more, or 0.8% by mass or more, based on the total mass of solids in the coating liquid. The binder content in the coating liquid may be, for example, 10% by mass or less, 8% by mass or less, 6% by mass or less, 4% by mass or less, or 2% by mass or less, based on the total mass of solids in the coating liquid.

[0083] In the first step of the manufacturing method for the positive electrode, methods for applying the coating liquid to the current collector include application by an applicator, application by spraying, and screen printing.

[0084] In the first step of the method for manufacturing the positive electrode, the drying temperature may be 50°C or higher, or 70°C or higher, and may be 150°C or lower, or 130°C or lower. In the first step of the method for manufacturing the positive electrode, the drying time may be 30 minutes or higher, or 2 hours or lower.

[0085] In the first step of the method for manufacturing the positive electrode, the thickness of the coating film is not particularly limited and may be adjusted as appropriate, for example, so that the thickness of the positive electrode material after the second step falls within the range described above.

[0086] The second step in the method for manufacturing the positive electrode may be a step of pressing the coating film so that the porosity of the positive electrode material is 30-40%. The pressing pressure (linear pressure) may be, for example, 10 kg / cm or more, or 30 kg / cm or more. Alternatively, the pressing pressure (linear pressure) may be, for example, 100 kg / cm or less, or 70 kg / cm or less.

[0087] In the second step of the positive electrode manufacturing method, the coating film may be further dried after pressing. The drying temperature may be 100°C or higher and 150°C or lower. The drying time may be 1 hour or more and 5 hours or less.

[0088] The battery according to this embodiment may include the positive electrode described above. The battery may also include the positive electrode, a negative electrode, and a separator. The separator may be positioned between the positive electrode and the negative electrode.

[0089] The negative electrode may include a current collector (negative electrode current collector) and a negative electrode material supported by the current collector. The negative electrode material may include an active material (negative electrode active material) and a binder.

[0090] Examples of negative electrode active materials include carbonaceous materials such as natural graphite, artificial graphite, graphite, activated carbon, coke, needle coke, fluid coke, mesophase microbeads, carbon fiber, and pyrolysis carbon. The content of the negative electrode active material in the negative electrode material may be, for example, 90% by mass or more, or 95% by mass or more, based on the total mass of the negative electrode material. Alternatively, the content of the negative electrode active material in the negative electrode material may be, for example, 99% by mass or less, or 98% by mass or less, based on the total mass of the negative electrode material.

[0091] The details of the binder in the negative electrode material may be the same as those of the binder in the positive electrode material described above. The binder content in the negative electrode material may be, for example, 0.5% by mass or more, or 1% by mass or more, based on the total mass of the negative electrode material. Alternatively, the binder content in the negative electrode material may be, for example, 5% by mass or less, based on the total mass of the negative electrode material.

[0092] Other additives in the negative electrode material may be the same as the other additives in the positive electrode material described above. The content of other additives in the negative electrode material may be, for example, 0.5% by mass or more and 3% by mass or less, based on the total mass of the negative electrode material.

[0093] The thickness of the negative electrode material may be, for example, 30 μm or more, or 100 μm or less.

[0094] The negative electrode current collector may be a metal foil or a metal plate. Examples of metals contained in the metal foil or metal plate include copper, stainless steel, aluminum, nickel, iron, and titanium. The thickness of the negative electrode current collector may be, for example, 1 μm or more, or 5 μm or more. Alternatively, the thickness of the negative electrode current collector may be, for example, 30 μm or less, or 20 μm or less.

[0095] The thickness of the negative electrode may be, for example, 50 μm or more, or 100 μm or less.

[0096] A method for manufacturing a negative electrode may include a first step of applying a coating solution containing a negative electrode active material, a binder, and a liquid medium onto a negative electrode current collector and drying it to form a coating film containing the negative electrode active material and binder on the negative electrode current collector, and a second step of pressing the coating film to form a negative electrode material on the negative electrode current collector. The details of the negative electrode active material and binder in the coating solution in the method for manufacturing a negative electrode may be the same as those for the negative electrode material described above. The details of the liquid medium in the coating solution in the method for manufacturing a negative electrode may be the same as those for manufacturing a positive electrode.

[0097] The content of the negative electrode active material in the coating solution in the negative electrode manufacturing method may be, for example, 90% by mass or more, or 95% by mass or more, based on the total mass of solids in the coating solution. Alternatively, the content of the negative electrode active material in the coating solution in the negative electrode manufacturing method may be, for example, 99% by mass or less, or 98% by mass or less, based on the total mass of solids in the coating solution.

[0098] The binder content in the coating solution in the negative electrode manufacturing method may be, for example, 0.5% by mass or more, or 1% by mass or more, based on the total mass of solids in the coating solution. Alternatively, the binder content in the coating solution in the negative electrode manufacturing method may be, for example, 5% by mass or less, based on the total mass of solids in the coating solution.

[0099] In the first step of the negative electrode manufacturing method, methods for applying the coating liquid to the negative electrode current collector include application by an applicator, application by spraying, and screen printing.

[0100] In the first step of the negative electrode manufacturing method, the drying temperature may be 50°C or higher and 100°C or lower. In the first step of the negative electrode manufacturing method, the drying time may be 30 minutes or higher and 3 hours or lower.

[0101] In the second step of the negative electrode manufacturing method, the press pressure (linear pressure) may be 5 kg / cm or more, or 10 kg / cm or more, and may be 40 kg / cm or less, or 30 kg / cm or less.

[0102] In the second step of the negative electrode manufacturing method, the coating film may be further dried after pressing. The drying temperature may be 50°C or higher and 100°C or lower. The drying time may be 30 minutes or higher and 3 hours or lower.

[0103] The separator may contain a polymer. Examples of polymers include polyolefins, polyamides, and polyesters. The thickness of the separator may be 80 μm or more, and may be 100 μm or less. The separator may be porous.

[0104] The method for manufacturing the battery in this embodiment is not particularly limited and can be carried out using conventionally known methods for manufacturing secondary batteries, but it can also be manufactured by the following method, for example. That is, a separator is placed between the positive electrode and the negative electrode, and a non-aqueous electrolyte is poured into the gap between the positive electrode, the negative electrode and the separator until it is sufficiently saturated.

[0105] The gravimetric energy density of the battery may be, for example, 50 Wh / kg or more, 60 Wh / kg or more, or 70 Wh / kg or more, from the viewpoint of further improving battery capacity. Furthermore, from the viewpoint of suppressing manufacturing costs, the gravimetric energy density of the battery may be, for example, 100 Wh / kg or less, 90 Wh / kg or less, or 80 Wh / kg or less.

[0106] The battery in this embodiment may be for use in a hybrid electric vehicle (HEV). The battery in this embodiment has a positive electrode material porosity of 30-40% and is compact. Furthermore, the battery in this embodiment has low internal resistance and excellent discharge rate characteristics. Therefore, the battery in this embodiment is suitable as a battery for HEVs as it can easily improve the acceleration performance of HEVs.

[0107] The battery according to this embodiment is suitable as a battery for HEVs, but it may also be used for other applications, such as consumer electronics. The battery according to this embodiment has a positive electrode material with a porosity of 30-40% and is lightweight, so it can be used to reduce the weight of consumer electronics. Examples of consumer electronics include power tools, laptop computers, electric bicycles, smartphones, digital cameras, and mobile batteries. [Examples]

[0108] The present disclosure will be described in more detail below based on the following examples. However, the present disclosure is not limited to the following examples.

[0109] <Example 1> (Carbon black slurry) Li-500 (BET specific surface area: 301m 2 A slurry containing Li-500 was prepared by adding N-methyl-2-pyrrolidone (hereinafter also referred to as "NMP") as the dispersion medium (1 / g, primary particle size: 19 nm) and hydrogenated nitrile butadiene rubber (manufactured by ARLANXEO, product name "THERBAN® AT3404") as the dispersant. 89.0 parts by mass of NMP was mixed with 2.25 parts by mass of hydrogenated nitrile butadiene rubber and 15.0 parts by mass of Li-500, and stirred for 120 minutes in a planetary mixer (manufactured by Primix Co., Ltd., product name "Hibis Disperser Mix 3D-5") to prepare a slurry containing Li-500. The obtained slurry was placed into a bead mill (manufactured by Ashizawa Finetech Co., Ltd., product name "Mugen Flow® MGF2-ZA") equipped with zirconia beads (diameter 0.5 mm) and subjected to dispersion treatment. After dispersion treatment, the zirconia beads were removed by filtration to prepare a slurry of Li-500.

[0110] (Coating liquid for positive electrode material) A slurry of Li-500 prepared using Li-500, with an average diameter of 10 nm and a BET specific surface area of ​​230 m². 2 An NMP dispersion of carbon nanotubes (JEIO, product name "JENOTUBE10B") with a specific surface area of ​​0.04 per g and average diameter / BET was prepared. In addition, lithium nickel manganese cobalt oxide (Ningbo Rongbai, average particle size 11 μm) was prepared as the active material, polyvinylidene fluoride NMP solution (Solvay, product name "SOLEF5130") as the binder, and NMP as the dispersion medium. The solution was prepared so that the active material was 98.5% by mass, carbon black was 0.15% by mass, carbon nanotubes were 0.35% by mass, and binder was 1.0% by mass. NMP was added until the viscosity was suitable for coating, and the mixture was homogenized using a rotation-orbit mixer (Thinky Co., Ltd., product name "Awatori Rentaro ARV-310") to obtain a coating solution for the cathode material (content is based on the total amount of solids in the coating solution).

[0111] (positive electrode) A coating solution (NMP dispersion) for the prepared cathode material was deposited onto one side of a 15 μm thick aluminum foil (manufactured by UACJ Corporation) using an applicator to create a laminate. The laminate was then pre-dried in a dryer at 105°C for 1 hour to completely remove the NMP. Next, the dried laminate was pressed in a roll press at a linear pressure of 50 kg / cm to adjust the overall thickness of the laminate to 48 μm. Finally, the laminate was vacuum-dried at 120°C for 3 hours to completely remove residual moisture, obtaining a cathode comprising a current collector made of aluminum foil and the cathode material. The carbon black content in the cathode material was 30% by mass, based on the total content of carbon black and carbon nanotubes. The basis weight of the cathode material was 10 mg / cm². 2 The porosity of the positive electrode material was 35.3%. The porosity of the positive electrode material was calculated using the following formula. The measured density of the positive electrode material was calculated by measuring the weight and volume of the positive electrode material punched out to a diameter of φ14 mm. Porosity = {1 - (measured density of cathode material) / (theoretical density of cathode material)} × 100

[0112] (Negative electrode) Pure water (manufactured by Kanto Chemical Co., Ltd.) was prepared as the solvent, artificial graphite (manufactured by Resonac Co., Ltd., product name "MAG-D") as the negative electrode active material, styrene-butadiene rubber (manufactured by Zeon Corporation, product name "BM-400B", hereinafter also referred to as "SBR") as the binder, and carboxymethylcellulose (manufactured by Daicel Corporation, product name "D2200", hereinafter also referred to as "CMC") as the dispersant. Next, based on the total amount of solids in the coating solution, CMC was weighed and mixed so that it accounted for 1% by mass and artificial graphite for 97% by mass. Pure water was added to this mixture, and the mixture was mixed until homogeneous using a rotary-orbit mixer (manufactured by Thinky Co., Ltd., product name "Awatori Rentaro ARV-310") to obtain a uniform mixture. Next, SBR was weighed to 2% by mass based on the total amount of solids in the coating solution, added to the resulting mixture, and mixed until uniform using a rotation-orbit mixer (manufactured by Thinky Co., Ltd., product name "Awatori Rentaro ARV-310") to obtain a coating solution for the negative electrode material. Next, the coating solution for the negative electrode material was deposited onto a 10 μm thick copper foil (manufactured by UACJ Corporation) using an applicator to create a laminate, which was then left to stand in a dryer and pre-dried at 80°C for 1 hour. Next, it was pressed with a roll press at a linear pressure of 20 kg / cm to adjust the total thickness of the laminate to 70 μm. Finally, it was vacuum dried at 80°C for 3 hours to completely remove residual moisture and obtain a negative electrode comprising a current collector made of copper foil and a negative electrode material layer.

[0113] (battery) In a dry room controlled to a dew point of -50°C or lower, the fabricated positive electrode was processed to 40 x 40 mm and the fabricated negative electrode to 44 x 44 mm. Then, an aluminum tab was welded to the positive electrode and a nickel tab to the negative electrode. The positive electrode material surface and the negative electrode material surface were positioned to face each other in the center, and a 45 x 45 mm polyolefin microporous membrane was placed between the positive and negative electrodes. Next, a sheet-like outer covering cut and processed to a 70 x 140 mm square was folded in half at the center of its long side. Then, the outer covering was positioned so that the aluminum tab for the positive electrode and the nickel tab for the negative electrode were exposed to the outside of the outer covering, and the laminate of the positive electrode / polyolefin microporous membrane / negative electrode was sandwiched between the folded outer covering. Next, using a heat sealer, two sides of the outer casing, including the side where the aluminum tab for the positive electrode and the nickel tab for the negative electrode are exposed, were heat-fused together. Then, 1 g of electrolyte (a solution containing ethylene carbonate / diethyl carbonate = 1 / 2 (volume ratio) and 1 M LiPF6 solution, manufactured by Kishida Chemical Co., Ltd.) was poured into the unfused side to allow the electrolyte to fully permeate the positive electrode, negative electrode, and polyolefin microporous membrane. Finally, the remaining side of the outer casing was heat-fused together using a vacuum heat sealer while reducing the internal pressure to obtain a lithium-ion secondary battery.

[0114] <Example 2> A lithium-ion secondary battery was fabricated in the same manner as in Example 1, except that the coating solution for the cathode material was prepared to contain 0.25% by mass of carbon black and 0.25% by mass of carbon nanotubes. The carbon black content in the cathode material was 50% by mass, based on the total content of carbon black and carbon nanotubes. The basis weight of the cathode material was 10 mg / cm³. 2 The porosity of the positive electrode material was 35.3%.

[0115] <Comparative Example 1> A lithium-ion secondary battery was fabricated in the same manner as in Example 1, except that the coating solution for the cathode material was prepared to contain 0.10% by mass of carbon black and 0.40% by mass of carbon nanotubes. The carbon black content in the cathode material was 20% by mass, based on the total content of carbon black and carbon nanotubes. The basis weight of the cathode material was 10 mg / cm³. 2 The porosity of the positive electrode material was 35.3%.

[0116] <Comparative Example 2> A lithium-ion secondary battery was fabricated in the same manner as in Example 1, except that the coating solution for the cathode material was prepared to contain 0.35% by mass of carbon black and 0.15% by mass of carbon nanotubes. The carbon black content in the cathode material was 70% by mass, based on the total content of carbon black and carbon nanotubes. The basis weight of the cathode material was 10 mg / cm³. 2 The porosity of the positive electrode material was 35.3%.

[0117] <Comparative Example 3> A lithium-ion secondary battery was fabricated in the same manner as in Example 1, except that the linear pressure of the roll press machine was changed so that the porosity of the positive electrode material was 44%. The basis weight of the positive electrode material was 10 mg / cm². 2 That was the case.

[0118] <Comparative Example 4> A lithium-ion secondary battery was fabricated in the same manner as in Example 1, except that the linear pressure of the roll press machine was changed so that the porosity of the positive electrode material was 26.9%. The basis weight of the positive electrode material was 10 mg / cm². 2 That was the case.

[0119] (Battery evaluation) [Internal resistance] The fabricated batteries were charged at 25°C under constant current and voltage conditions, limited to 4.3V and 0.2C, and then discharged to 3.0V under a constant current of 0.2C. Next, they underwent 5 charge / discharge cycles under the same conditions, and then were charged to a 30% charge level. Afterward, impedance measurements were performed at a frequency range of 10MHz to 0.001Hz and an oscillating voltage of 5mV to determine the internal resistance (labeled "SOC30" in Table 1). Similarly, the internal resistance was measured for batteries charged to 50% and 70% charge levels (labeled "SOC50" and "SOC70" in Table 1, respectively). The results of the internal resistance measurements are shown in Table 1.

[0120] [Discharge rate characteristics (rate capacity maintenance rate)] The fabricated batteries were charged at 25°C under constant current and voltage conditions of 4.3V and 0.2C limit, and then discharged to 3.0V with a constant current of 0.2C. Next, they were recharged again under constant current and voltage conditions of 4.3V and 0.2C limit, and then discharged to 3.0V with a constant current of 0.2C, and the discharge capacity at this time was measured. Subsequently, the recharge conditions were set to constant current and voltage of 4.3V and 0.2C limit, while the discharge current was gradually changed to 0.5C, 1C, 2C, and 3C. The recharge and discharge cycles were repeated, and the discharge capacity for each discharge current was measured. As an indicator of the battery's discharge rate characteristics, the capacity retention rate at 3C discharge compared to 0.2C discharge was calculated as the rate capacity retention rate. The calculation results of the rate capacity retention rate are shown in Table 1.

[0121] [Table 1]

Claims

1. It includes a current collector and a positive electrode material supported by the current collector, The positive electrode material contains carbon black, carbon nanotubes, an active material, and a binder. The carbon black content in the cathode material is 25 to 60% by mass, based on the total content of the carbon black and carbon nanotubes. A positive electrode having a porosity of 30-40% of the positive electrode material.

2. The carbon black is 100 to 400 m 2 The positive electrode according to claim 1, having a BET specific surface area of ​​1 / g, a crystallite size (Lc) of 15 to 26 Å, and an average primary particle diameter of 17 to 30 nm.

3. The positive electrode according to claim 1, wherein the carbon nanotubes have an average diameter of 5 to 15 nm.

4. The basis weight of the aforementioned positive electrode material is 7.5 to 12.5 mg / cm². 2 The positive electrode according to claim 1.

5. A battery comprising the positive electrode described in any one of claims 1 to 4.

6. The battery according to claim 5, for use in hybrid electric vehicles or consumer products.

7. A manufacturing method for producing a positive electrode according to any one of claims 1 to 4, A first step involves applying a coating solution containing carbon black, carbon nanotubes, active material, binder, and liquid medium onto a current collector and drying it to form a coating film on the current collector containing the carbon black, carbon nanotubes, active material, and binder. A second step involves pressing the coating film to form the positive electrode material on the current collector, Equipped with, The carbon black content in the coating solution is 25 to 60% by mass, based on the total content of the carbon black and carbon nanotubes. A method for manufacturing a positive electrode, wherein the second step is to press the coating film so that the porosity of the positive electrode material is 30 to 40%.

Citation Information

Patent Citations

  • Nonaqueous electrolytic material

    JP2001126733A